Costimulation induced phosphorylation of L-plastin facilitates surface transport of the T cell activation molecules CD69 and CD25 - Wabnitz, Guido H.; Köcher, Thomas; Lohneis, Philipp; Stober, Christoph Bruno; Konstandin, Mathias; Funk, Beate; Sester, Urban; Wilm, Matthias; Klemke, Martin; Samstag, Yvonne (European journal of immunology, 2007)
Rearrangements in the actin cytoskeleton play a pivotal role for costimulation-induced formation of the immunological synapse and T cell activation. Yet, little is known about the actin-binding proteins that link costimulation to rearrangements in the actin cytoskeleton. Here we demonstrate that phosphorylation of the actin bundling protein L-plastin in response to costimulation through TCR/CD3 plus CD2 or CD28, respectively, is important for the activation of human peripheral blood T lymphocytes (PBT). Mass spectrometry and site-directed mutagenesis revealed that Ser5 represents the only phospho-acceptor site of L-plastin in PBT. Wild-type L-plastin (wt-LPL) and a non-phosphorylatable 5A-L-plastin (5A-LPL) equally relocalized to the immunological synapse between PBT and APC. Yet importantly, cells expressing 5A-LPL showed a significantly lower expression of the T cell activation molecules CD25 and CD69 on the cell surface than cells expressing wt-LPL. This effect is due to a failure in the transport of CD25 and CD69 to the cell surface since the total amount of these proteins within the cells remained unchanged. In conclusion, phosphorylation of the actin bundling protein L-plastin represents a so-far-unknown mechanism by which costimulation controls the transport of activation receptors to the T cell surface.
Gesehen am 25.06.2021